Identification and Clinical Validation of High HSP60 Expression Predicts Poor Prognosis in Patients with Ovarian Cancer - Zheng M; Li S; Deng J; Huang C; Zhang H (International Journal of General Medicine)
Min Zheng,1,* Shaoxing Li,1,* Jie Deng,1 Chaolin Huang,1 Hua Zhang2 1Department of Gynecology and Obstetrics, Clinical Medical College and The First Affiliated Hospital of Chengdu Medical College, Chengdu, People’s Republic of China; 2Department of Rehabilitation Medicine, Clinical Medical College and The First Affiliated Hospital of Chengdu Medical College, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua Zhang; Chaolin Huang, Department of Gynecology and Obstetrics, Clinical Medical College and The First Affiliated Hospital of Chengdu Medical College, No. 278, The Middle Section of Baoguang Avenue, Xindu District, Chengdu City, Sichuan Province, 610500, People’s Republic of China, Email 2508034576@qq.com; huangchaolin1006@163.comObjective: This study aimed to investigate the clinical significance of heat shock protein 60 (HSP60) expression in ovarian cancer and evaluate its correlation with patient survival outcomes.Methods: A total of 260 ovarian cancer patients diagnosed between 2017 and 2019 were enrolled. Immunohistochemistry was performed to assess HSP60 expression in tumor tissues. Patients were categorized into high- or low-HSP60 expression groups based on immunohistochemical staining intensity. The correlation between HSP60 expression status and the clinicopathological features of ovarian cancer patients was analyzed. Kaplan-Meier survival curves and Cox regression models were utilized to evaluate overall survival and disease-free survival.Results: HSP60 expression was significantly higher in ovarian cancer tissues compared to normal ovarian tissues. High HSP60 expression was associated with larger tumor size, advanced FIGO stage, and increased lymph node metastasis. Patients with high HSP60 expression exhibited significantly shorter overall survival and disease-free survival than those with low expression. Multivariate Cox analysis identified HSP60 as an independent prognostic factor for both overall survival and disease-free survival.Conclusion: High HSP60 expression is associated with poor prognosis and aggressive tumor characteristics in ovarian cancer. HSP60 may serve as a valuable biomarker for prognosis and a potential therapeutic target. Further randomized clinical trials are warranted to explore its role in ovarian cancer progression and treatment strategies.Keywords: HSP60, ovarian cancer, disease-free survival, overall survival, Cox regression model